Efficacy of Levobupivacaine Versus Levobupivacaine Plus Dexmedetomidine Infiltration for Post-Tonsillectomy Analgesia: A Randomized Controlled Trial - Ghada Mohammad Abo Elfadl; Marwa Mahmoud AbdelRady; Hany M. Osman; Mohamed Omar Gad; Nessren M. Abd el-Rady; Wesam Nashat Ali (Pain Research and Management)
Background. The study evaluated the analgesic effects of levobupivacaine infiltration in the tonsil bed, and a combination of levobupivacaine and dexmedetomidine in patients undergoing tonsillectomy. Methods. Ninety children (ages 3 to 7 years) who were scheduled for a tonsillectomy were allocated randomly into two groups. (L Group): peritonsillar infiltration with 0.25% levobupivacaine (2 ml + 0.5 ml saline 0.9% per tonsil). (LD Group): levobupivacaine 0.25% (2 ml) plus dexmedetomidine 1 μg/kg diluted in 1 ml saline 0.9% (0.5 ml in each tonsil), and administered by peritonsillar infiltration (2.5 ml per tonsil) following intubation 3–5 minutes before operation. To avoid bias, infiltrate a total volume of 2.5 ml in each tonsil. The first analgesic request time was the primary outcome, with postoperative pain score, total analgesic consumption, total oral intake, sedation, and side effects as secondary outcomes. Results. The first rescue analgesia time in the LD group was longer (644.31 ± 112.89 min) than in the L group (551.51 ± 146.16 min, P-value <0.001). The number of patients who required >1 analgesic dose in the L group (n = 13) was higher than in the LD group (n = 5). The LD group consumes a lower total dose of IV paracetamol in the first 24 hours postoperatively (321.89 ± 93.25 mg) than the L group (394.89 ± 183.71 mg, P<0.00-value < 0.050). On the first day postoperatively, patients in the LD group had a higher total oral intake (P<0.001). Except for a slight increase in laryngospasm in the L group, there were no side effects. Conclusions. The Children’s peritonsillar infiltration of levobupivacaine and dexmedetomidine improved postoperative pain after adenotonsillectomy. The topically applied levobupivacaine and dexmedetomidine were concomitant with no systemic effects, greater total oral intake on the first day postoperative, and higher family satisfaction.